KEDUDUKAN SAKSI DALAM PEMBUATAN AKTA JUAL BELI HAK ATAS TANAH DI HADAPAN PEJABAT PEMBUAT AKTA TANAH - Kadek Yudhi Aditya Putra; Ibrahim R.; Kadek Sarna (Kertha Negara : Journal Ilmu Hukum, 2013)
Considering State Indonesia is Agricultural Country and most its societyhave subsistence of agricultural produce, hence increasing also requirement ofland; ground human being will till often we meet the existence of land; groundsales transaction. In this case, such land; ground in congeniality of yuridis of is socalledrights. Such as those which we know, in land; ground sales transaction toget authenticity about ownership of hence require to be made by an madeagreement before Functionary of Maker of Act of land. Purchasing and sellingagreement happened caused by second agreement split side, good regarding objectwhich is sold and also his price. Related of solution in this research, namelyresponsibility a eyewitness in making of sale act buy, land right beforeFunctionary Of Maker of Act of land (PPAT) and authenticity from an sale actbuy land; ground if when related to domicile eyewitness.